Differences in anti-inflammatory effect of immature and mature of Rubus coreanus fruits on LPS-induced RAW 264.7 macrophages via NF-κB signal pathways - Kyung Hye Seo; Ji Yeon Lee; Jeong-Yong Park; Gwi Yeong Jang; Hyung Don Kim; Young- Seob Lee; Dong Hwi Kim (BMC, 2019)
Abstract Background Rubus coreanus fruit (RF) has been used as a traditional medicine formulation to treat various diseases including diarrhea, asthma, and cancer in East Asia (Korea, China, and Japan). RF, which is native to Korea, has a larger fruit size than that of exotic species. In this study, we aimed to compare the anti-inflammatory activities of immature and mature RF extracted with different solvents. Methods Mature and immature RF (MRF and IRF) were extracted with 30% ethanol, 70% ethanol and water at room temperature. The antioxidant activity was determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid (ABTS) assays. Anti-inflammatory activity was determined by measuring nitric oxide (NO) production, expression of inflammatory proteins (inducible NO synthase [iNOS], cyclooxygenase [COX]-2, nuclear factor [NF]-κB, and inhibitor of NF-κB [IκB]), and inflammatory cytokines using polymerase chain reaction in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages. Results The IRF 30% ethanol extract showed higher radical scavenging activity in DPPH and ABTS assays (half-maximal inhibitory concentration [IC50] 16.0 ± 0.5 and 15.9 ± 0.4) than MRF did. In addition, the IRF 30% ethanol extract (200 μg/mL) significantly reduced the production of the inflammatory mediator NO by approximately 80% and inhibited iNOS, COX-2, phosphorylated (p)-IκB, and p-NF-κB activation compared with MRF. Moreover, IRF extract decreased the inflammatory cytokines tumor necrosis factor-α, interleukin (IL)-1β, and IL-6 compared with the MRF extract. Conclusions This study revealed that IRF showed more beneficial effects than MRF did in LPS-stimulated RAW 264.7 macrophages, suggesting that IRF may be a useful anti-inflammatory agent.